2020
DOI: 10.18805/ag.d-5136
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Cluster Front Line Demonstrations in Chickpea (Cicer arietinum L.) for Productivity Enhancement under Rainfed Vertisols of YSR District Andhra Pradesh

Abstract: Cluster FLDs were organized by Krishi Vigyan Kendra, Utukur in rabi bengalgram during three consecutive years of 2013-14, 2014-15 and 2015-16 under rainfed vertisols farming situation in an area of 52 ha. at 94 locations. At every demonstration site improved management practices viz. improved variety with high yield potential and drought tolerance (Nandyal sanaga-1), Compartmental bunding (8 m x 5m), Soil test based integrated balanced nutrition: sulphur granules @ 10 kg ha-1, zinc sulphate @ 20 kg ha-1 as bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly,Samant (2017);Verma et al (2016) andMitra et al (2014) reported that FLDs on rice recorded maximum net returns with a high B: C ratio Mubark and Shakoor (2019). also obtained maximum gross returns, net returns and B: C ratio in FLDs with improved technologies in rice Madanmohan et al (2021). andJayalakshmi et al (2021) observed higher gross returns, net returns and benefit-cost ratio in demonstrations as compared to farmer's practice.…”
mentioning
confidence: 82%
“…Similarly,Samant (2017);Verma et al (2016) andMitra et al (2014) reported that FLDs on rice recorded maximum net returns with a high B: C ratio Mubark and Shakoor (2019). also obtained maximum gross returns, net returns and B: C ratio in FLDs with improved technologies in rice Madanmohan et al (2021). andJayalakshmi et al (2021) observed higher gross returns, net returns and benefit-cost ratio in demonstrations as compared to farmer's practice.…”
mentioning
confidence: 82%
“…The similar results were also reported by (Daniela et al, 2017) [2] and Mubark and Shakoor (2019) [7] also obtained maximum gross returns, net returns and B: C ratio in FLDs with improved technologies in rice. Madanmohan et al, (2021) [6] and Jayalakshmi et al, (2021) [5] observed higher gross returns, net returns and benefit-cost ratio in demonstrations as compared to farmer's practice. www.extensionjournal.com…”
Section: Economics Of Paddy Cultivationmentioning
confidence: 99%